2020
DOI: 10.3855/jidc.11834
|View full text |Cite
|
Sign up to set email alerts
|

Natural products and polysorbates: Potential Inhibitors of biofilm formation in Pseudomonas aeruginosa

Abstract: Introduction: With all the challenges super bugs are imposing, biofilm formation opens the door against various more complicated challenges. Such issue may be highlighted with the ability of the latter to render the antibiotics hardly accessible to bacterial cells and sheds the light on the importance of finding antibiofilm formers. Therefore, we assessed the inhibitory effect of natural product extracts (ginger, wild blueberry) and polysorbates (PS20, PS80) on biofilm formation at the molecular level. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Interestingly, the treatment with 256.00 µg/mL of KLRE showed an inhibitory effect on both the biofilm formation as well as the metabolic activity of standard and MRSA strains. These findings are consistent with other studies that have proved the efficacy of natural products in inhibiting the development of biofilm [ 42 , 43 , 44 ]. Concerning that, in our previous paper, we demonstrated the suppressive action of walnut ( Juglans regia ) pellicle extract on growth, biofilm formation, and cell viability of coagulase-negative staphylococci (CoNS) [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, the treatment with 256.00 µg/mL of KLRE showed an inhibitory effect on both the biofilm formation as well as the metabolic activity of standard and MRSA strains. These findings are consistent with other studies that have proved the efficacy of natural products in inhibiting the development of biofilm [ 42 , 43 , 44 ]. Concerning that, in our previous paper, we demonstrated the suppressive action of walnut ( Juglans regia ) pellicle extract on growth, biofilm formation, and cell viability of coagulase-negative staphylococci (CoNS) [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…Natural products have recently attracted increased attention due to their safety and antibiofilm effects. Recent studies have shown that gingerols, proanthocyanins, and condensed tannins, which are extracted from Ginger (Zingiber Officinale) and wild blueberry (Vaccinium Angustifolium), have antibiofilm effects (Miari et al, 2020). Topa et al showed that Cinnamaldehyde could disrupt biofilm formation and the swarming motility of P. aeruginosa (Topa et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Both compounds (crude extraction or methanolic fraction) interfere with hydrophobicity, between dental surface-bacterial interactions, through flavonoids, which reduce the enzyme GTFase and AG I / II, during synthesis / adherence, mainly of insoluble and dependent Glucans sucrose. Furthermore, the sites of bacterial binding, pH and integrity of exopolysaccharides are disturbed, in the formation of the climax community, disrupting pathogenicity and the sensing quorum (functioning as an anticariogenic), in addition to the expression of bacterial genes (Hasan et al, 2015;Miari et al, 2020).…”
Section: Discussionmentioning
confidence: 99%